Air Rebusan Kaktus Pakis Giwang (Euphorbia Milli Ch Des Moulins) Sebagai Obat Alternatif Hepatitis B (Antihepatitis) Pada Hewan Coba Tikus Putih (Rattus Norvegicus) - Lalu Sri Gede; Siti zaetun (Poltekkes Kemenkes Mataram, 2018)
Not many people know the benefits of forbia ornamental plants. One of the stems is an alternative medicine for hepatitis. Hepatitis is an inflammation of the liver caused by various factors. One of them is a viral infection to determine the effectiveness of boiled cactus fern cactus (Euphorbia milli Ch des Moulins) as antihepatitis in white mice (Rattus norvegicus). Experimental (true experiment) to determine the effectiveness of giving boiled cactus stem stud water (Euphorbia milli Ch des Moulins) and interferol as anti hepatitis B virus in white mice (Rattus norvegicus) as control controls in white mice. Post-test only controlled group design study design. The sample size of 30 male white rats (Rattus norvegicus) was grouped into 2. The first group of controls was given antihepatitis (Interferon) and the second group was given boiled water with cactus stud earrings. Data were analyzed by the Independent Sample T Test 95% confidence level (Pα 0.05). Point-of-care testing (POCT) (hepatitis in the group of rats before being given fern cactus stew water studs (Euphorbia milli Ch des Moulins) was negative. In the group of rats given antihepatitis (Interferon) according to the dose in the control group for 1 week still gave a negative result: There was 1 result that was given and given 2 weeks of cactus fern boiled water negative results.The results of the analysis could not conclude because of the negative results so it was suggested to test HBV on another try like a squirrel to get maximum results Because mice are not hosts for the hepatitis B virus.